Desenvolvimento de uma nova rota de síntese hidrotermal assistida por micro-ondas para a obtenção de nanopartículas de espinélios de manganês e lítio dopados com alumínio para aplicação em baterias de íons lítio - Falqueto, Juliana Bruneli (2018)
Spinel of manganese and lithium undoped and doped with aluminum were obtained by an unpublished, energy saving, short time, and low temperature synthesis: microwave-assisted hydrothermal route. Undoped spinel was synthesized using KMnO4, LiOH, and acetone. The reaction was carried out in a microwave reactor at 140 °C under constant magnetic stirring for 5 min. After that, it was submitted to a new microwave-assisted hydrothermal treatment, called ionic exchange, in a LiOH solution at 140 °C under constant magnetic stirring for 10 min. Finally, it was submitted to a heat treatment on a conventional microwave oven for 4 min. In order to obtain the spinels doped with aluminum, different routes of synthesis and aluminum proportions were studied. Doped spinels were obtained under the same synthesis conditions as the undoped spinel, with the addition of Al(NO3)3 in the proportion in mol of 1.000 Mn : 0.075 Al. The influence of the ionic exchange on the doping process was investigated using three different routes: without ionic exchange and ionic exchange with or without Al(NO3)3. All materials exhibited high intensity peaks on X-ray diffractograms (XRD), in accordance solely to the crystallographic pattern JCPDS 35-0782, referring to the LiMn2O4 of cubic phase. The peaks of higher intensity on the diffractograms referring to the spinel phase resulted in shifts to higher values of the angles 2θ, indicating the substitution of Mn3+ by Al3+ of smaller ionic radius. The SEM micrographs indicated the predominance of faceted structures with nanometric particle size between 30 and 50 nm and homogeneous distribution. Quantified by ICP analyses, all the doped spinels presented significant values of aluminum in mass percentage, which confirms doping. Due to high crystallinity, no phase segregation, lower doping content, and higher initial specific capacity, the route with ionic exchange without Al(NO3)3 was chosen to investigate the variation on the aluminum proportion. With this method, two other spinels were synthesized using the mol proportion of Mn : Al of 1.000 : 0.050 and 1.000 : 0.025. The XRD confirmed the absence of any secondary phase containing aluminum and/or potassium, and again the peaks of higher intensity showed shifts to higher values of the angles 2θ, which indicate doping. The mapping images obtained by EDX indicated that the aluminum element is present in the homogeneous way in all extension of the doped spinels. In the cyclic voltammetries characteristic profiles of the spinel were observed with higher peak currents values for spinels doped with lower contents of aluminum. The doped spinel with lower contents of aluminum showed the highest value of specific capacity (100 mA h g-1) at a rate C/10. In addition, because it was synthesized by an unpublished method and formation of only one crystalline phase and size of ~40 nm with homogeneous distribution, this material was promising for the continuity of the electrochemical tests.